The Cultural Politics of the New American Studies - Rowe, John Carlos (Open Humanities Press, 2012)
In The Cultural Politics of the New American Studies, leading American Studies scholar John Carlos Rowe responds to two urgent questions for intellectuals. First, how did neoliberal ideology use the issues of feminism, gay rights, multiculturalism, transnationalism and globalization, class mobility, religious freedom, and freedom of speech and cultural expression to justify a new -American Exceptionalism,- designed to support U.S. economic, political, military, and cultural expansion around the world in the past two decades? Second, if neoliberalism has employed successfully various cultural media, then what are the best means of criticizing its main claims and fundamental purposes? Is it possible under these circumstances to imagine a -counter-culture,- which might effectively challenge neoliberalism or is such an alternative already controlled and contained by such labels as -political correctness,- -the far left,- -radicalism,- -extremism,- even -terrorism,- which in the popular imagination refer to political and social minorities, doomed thereby to marginalization? Rowe argues that the tradition of -cultural criticism- advocated by influential public intellectuals, like Edward Said, can be adapted to the new circumstances demanded by the hegemony of neoliberalism and its successful command of new media. Yet rather than simply honoring such important predecessors as Said, we need to reconceive the role of the public intellectual as more than just an -interdisciplinary scholar- but also as a social critic able to negotiate the different media.
English
Keywords: USA; Society & culture: general; american studies; neoliberal ideology; cultural criticism